Exploring unconventional targets in myofibroblast transdifferentiation outside classical TGF-β signaling in renal fibrosis - Lathan, Rashida (Frontiers in Physiology, 2024)
We propose that the key initiators of renal fibrosis are myofibroblasts which originate from four predominant sources—fibroblasts, pericytes, endothelial cells and macrophages. Increased accumulation of renal interstitial myofibroblasts correlates with an increase in collagen, fibrillar proteins, and fibrosis severity. The canonical TGF-β pathway, signaling via Smad proteins, is the central molecular hub that initiates these cellular transformations. However, directly targeting these classical pathway molecules has proven challenging due their integral roles in metabolic process, and/or non-sustainable effects involving compensatory cross-talk with TGF-β. This review explores recently discovered alternative molecular targets that drive transdifferentiation into myofibroblasts. Discovering targets outside of the classical TGF-β/Smad pathway is crucial for advancing antifibrotic therapies, and strategically targeting the development of myofibroblasts offers a promising approach to control excessive extracellular matrix deposition and impede fibrosis progression.